Evidence-Based Marketing for Academic Librarians - Yoo-Seong Song (Evidence Based Library and Information Practice, 2006)
Objective - In developing marketing strategies for the Business & Economics Library (BEL) at the University of Illinois at Urbana-Champaign (UIUC), a survey was designed to answer the following questions: - Should BEL develop marketing strategies differently for East Asian business students? - What services do graduate business students want to receive from BEL? - With whom should BEL partner to increase visibility at the College of Business? Marketing research techniques were used to gather evidence upon which BEL could construct appropriate marketing strategies. Methods - A questionnaire was used with graduate business students enrolled at UIUC. The survey consisted of four categories of questions: 1) demographics, 2) assessment of current library services, 3) desired library services, and 4) research behavior. The data were analyzed using desriptive statistics and hypothesis testing to answer the three research questions. Results - East Asian business students showed similar assessment of current services as non-East Asian international business students. Survey results also showed the graduate business students had low awareness of current library services. The Business Career Services Office was identified as a co-branding partner for BEL to increase its visibility. Conclusion - A marketing research approach was used to help BEL make important strategic decisions before launching marketing campaigns to increase visibility to graduate business students at UIUC. As a result of the survey, a deeper understanding of graduate business students' expectations and assessment of library services was gained. Students' perceptions became a foundation that helped shape marketing strategies for BEL to increase its visibility at the College of Business. Creating marketing strategies without concrete data and analysis is a risky endeavor that librarians, not just corporate marketers, should avoid.